Image guided adaptive brachytherapy with combined intracavitary and interstitial technique improves the therapeutic ratio in locally advanced cervical cancer: Analysis from the retroEMBRACE study. Issue 3 (September 2016) - Fokdal, Lars; Sturdza, Alina; Mazeron, Renaud; Haie-Meder, Christine; Tan, Li Tee; Gillham, Charles; Šegedin, Barbara; Jürgenliemk-Schultz, Ina; Kirisits, Christian; Hoskin, Peter; Pötter, Richard; Lindegaard, Jacob C.; et al.
Abstract: Background and purpose: Image guided adaptive brachytherapy (IGABT) using intracavitary applicators (IC) has led to a significant improvement of local control in locally advanced cervical cancer (LACC). Further improvement has been obtained with combined intracavitary/interstitial (IC/IS) applicators. The aim of this analysis was to evaluate the impact on local control and late morbidity of application of combined IS/IC brachytherapy in a large multicentre population. Material/methods: 610 patients with LACC from the retroEMBRACE study were included. Patients were divided into an IC group ( N  = 310) and an IC/IS group ( N  = 300). The IC/IS group was defined from the time point, when a centre performed IC/IS brachytherapy in more than 20% of cases. Results: With systematic usage of IC/IS the D90 of CTVHR increased from 83 ± 14 Gy to 92 ± 13 Gy ( p  < 0.01). No difference in doses to organs at risk was found. The 3-year local control rate in patients having a CTVHR volume ⩾ 30 cm 3 was 10% higher ( p  = 0.02) in the IC/IS group. No difference was found for CTVHR  < 30 cm 3 ( p  = 0.50). No significant difference in late morbidity was found between the IC/IS group and IC group. Conclusion: Combined IC/IS brachytherapy improves the therapeutic ratio in LACC by enabling a tumour specific dose escalation resulting in significantly higher local control in large tumours without adding treatment related late morbidity.